PENDIDIKAN KARAKTER DALAM AL-QUR’AN - Ibnu Fajar (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2019)
Religious education is delivered at the school level, in order to impart the basics of faith and devotion to God Almighty, the learners who aim to embody human piety and noble character, as well as generating an honest man, fair, ethical, ethical, mutual appreciates, discipline, harmonious and productive, both personal and social. Character education is very urgent need to be studied. It has long been understood that a Government condition is determined by the character of the people. The founders of this nation was repeatedly emphasized that the successful or failure of an experiment of the country will be determined by the values of character education attached to the personality of the inhabitants of the land. In this article will discuss how character education in the Qur'an? How the implementation of character education in Indonesia?